Microsporidia and Cryptosporidium in horses and donkeys in Algeria: detection of a novel Cryptosporidium hominis subtype family (Ik) in a horse - Laatamna, Abd Elkarim; Wagnerová, Pavla; Sak, Bohumil; Květoňová, Dana; Xiao, Lihua; Rost, Michael; McEvoy, John; Saadi, Ahmed Rachid; Aissi, Meriem; Kváč, Martin (Veterinary parasitology, 2015)
A total of 219 and 124 individual fecal samples of horses and donkeys, respectively, were screened for the presence of Cryptosporidium spp., Encephalitozoon spp., and Enterocytozoon bieneusi DNA by genus-specific nested PCR. Isolates were genotyped by sequence analysis of SSU rRNA, GP60, TRAP-C1, COWP, and HSP70 loci in Cryptosporidium, and the ITS region in microsporidia. Cryptosporidium spp. was detected on 3/18 horse farms and 1/15 farms where donkeys were kept. Overall, five (2.3%) horse and two (1.6%) donkey specimens were PCR positive for Cryptosporidium. Genotyping at SSU and GP60 loci revealed that three isolates from horses and donkeys were C. parvum subtype family IIaA16G1R1, one isolate from a horse was, C. muris RN66, and one isolate from a donkey was C. muris TS03. An isolate from a horse shared 99.4% and 99.3% similarity with Cryptosporidium hominis and C. cuniculus, respectively, at the SSU locus. This isolate shared 100% identity with C. hominis at the TRAP-C1, COWP, and HSP70 loci, and it was from the novel gp60 subtype family IkA15G1. Microsporidia were found on 6/18 horse and 2/15 donkey farms. E. bieneusi was identified in 6.8% (15/219) and 1.6% (2/124), and Encephalitozoon cuniculi was identified in 1.8% (4/219) and 1.6% (2/124), of horses and donkeys, respectively. Three genotypes of E. cuniculi (I, II and III) were detected in horses, and E. cuniculi genotype II was detected in donkeys. Four genotypes of E. bieneusi (horse1, horse 2, CZ3, D) were described in horses. An additional five horses and two donkeys were positive for E. bieneusi, but the isolated were not genotyped. Neither Cryptosporidium nor microsporidia prevalence were affected by sex, age, type of breeding, or whether the host was a horse or a donkey.
Keywords: Feces; Prevalence; genotyp; Cryptosporidium; Molecular prevalence; Cryptosporidiosis; Algeria; Genotype; Equidae; Donkeys; mužské pohlaví; prevalence; Microsporidiosis; Alžírsko; Encephalitozoon spp.; Horses; nemoci koní; ženské pohlaví; Microsporidia; zvířata; feces; Enterocytozoon bieneusi; koně; fylogeneze; Horse Diseases; Cryptosporidium spp.; Female; kryptosporidióza; mikrosporidióza; Phylogeny; Male; Animals